Correction: Yalçın, S.; Herdem, M.S. Optimizing EV Battery Management: Advanced Hybrid Reinforcement Learning Models for Efficient Charging and Discharging. Energies 2024, 17, 2883 - Sercan Yalçın; Münür Sacit Herdem (Energies, 2024)
In the original publication [...]